Islamic Mental Health Education for Adolescents in the Digital Era - Rosmalina, Asriyanti; Elrahman, Habib; Handayani, Hany; Affendi, Hazrul (Qualitative and Quantitative Research Center, 2023)
The development of the times in the current digital era has a positive and negative impact on the stages of adolescent development. Among the development of mental health for adolescents as individuals, the child development category in the final phase shows that their development still requires self-control guidelines for thinking and acting. Developing the health potential of adolescents can be done with Islamic mental health education. This study aims to discuss how important Islamic mental health education for adolescents in the digital era. The research method used is a type of library research. Based on the results of library research shows that teenagers who understand religious guidelines and carry out these understandings in everyday life, such as praying, remembrance, and reading the Qur'an, as well as good motivational support from parents, also make teenagers more able to easily socialize with the environment, able to control emotions in a variety of effective ways and increased concern for others of education by increasing its relevance in graduate employment. The contribution of this research provides information that Islamic mental health education can increase social awareness, control emotions, develop self-potential, and overcome adolescent problems.